2008
DOI: 10.1111/j.1365-2184.2008.00520.x
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of cell trafficking and metastases of paediatric rhabdomyosarcoma

Abstract: We established a model for visualization of experimental metastatic invasion and describe relevant tools for imaging childhood rhabdomyosarcoma metastases at the macroscopic and cellular levels. Imaging of cell trafficking visualized the behaviour of tumour cells and development of metastases by accumulation and extravasation of rhabdomyosarcoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…It is possible that the pattern of intracellular distribution of TdTom may depend on the cell type. Indeed, the localization of TdTom varies according to the cell type [29], and DsRed2, another type of RFP, shows dotted pattern in cells derived from rhabdomyosarcoma [30].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the pattern of intracellular distribution of TdTom may depend on the cell type. Indeed, the localization of TdTom varies according to the cell type [29], and DsRed2, another type of RFP, shows dotted pattern in cells derived from rhabdomyosarcoma [30].…”
Section: Discussionmentioning
confidence: 99%
“…In larger vessels, tumor cells attached to the vessel walls and an extravasation was observed 12 h later. The study concluded that the experimental metastatic invasion of rhabdomyosarcoma cells was caused by tumor cell accumulation and extravasation (45).…”
Section: Optical Imaging (Fluorescent Proteins)mentioning
confidence: 99%
“…For these studies, the infrared-fluorescent protein FP635 (mKATE) was cloned into the sneaking ligand constructs for their visualization (29,30). We examined the uptake of SLC1-FP635 into CHO_E cells by immunofluorescence microscopy.…”
Section: Nf-κb Inhibition Via E-selectin-mediated Endocytosis Of Slc1mentioning
confidence: 99%
“…In vivo imaging was used to prove the selective binding of SLC1 to cytokine-activated but not to resting endothelium in vivo (29,30). An epigastric vein in a cytokine-induced skin flap of live transgenic green fluorescent protein (GFP)-expressing mice was selected as the region of interest for SLC1 detection (Fig.…”
Section: Nf-κb Inhibition Via E-selectin-mediated Endocytosis Of Slc1mentioning
confidence: 99%